2015
DOI: 10.15453/2168-6408.1140
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Content Validity of Shore Handwriting Screening and Newly Developed Score Sheet With Pre-Kindergarten Students

Abstract: Background: Limited tools exist to measure handwriting readiness skills of pre-kindergarten students. This study was a preliminary exploration of content validity of the Shore Handwriting Screening (SHS) and the newly developed Score Sheet with the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOT-2) in 4-and 5-year-old pre-kindergarten students. Because socioeconomic status (SES) is known to impact handwriting skills, data from two different socioeconomic groups were collected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, to our knowledge, there is only one test for the detection of handwriting difficulties that can be used for children before the acquisition of handwriting: the Shore Handwriting Screening for Early Handwriting Development (SHS) [7], usable from the age of three, but information on its psychometric properties is lacking, and no normative sample has been developed [6]. Further to this, different studies [8][9][10][11][12][13][14] have shown that the score obtained on a well-known standardised reproduction test involving geometrical shapes, the Development Test of Visual-Motor Integration (VMI [15]), is a good predictor of handwriting skills.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to our knowledge, there is only one test for the detection of handwriting difficulties that can be used for children before the acquisition of handwriting: the Shore Handwriting Screening for Early Handwriting Development (SHS) [7], usable from the age of three, but information on its psychometric properties is lacking, and no normative sample has been developed [6]. Further to this, different studies [8][9][10][11][12][13][14] have shown that the score obtained on a well-known standardised reproduction test involving geometrical shapes, the Development Test of Visual-Motor Integration (VMI [15]), is a good predictor of handwriting skills.…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient visual-motor skills resulted in reversal writing letters, lack of ability to copy a word from a visual board onto paper, missing letters during copying activity, and the absence of space between written words (5,6). In addressing these, literature supported that occupational therapy interventions such as biomechanical, neuromotor, cognitive, sensory integrative, compensatory and positive collaboration consultation approaches are effective to treat handwriting difficulty among children (4,(7)(8)(9)(10)(11). Many handwriting intervention foundation frameworks can be integrated to guide professional practice within a specific setting.…”
Section: Introductionmentioning
confidence: 99%